The Mediating Role of Psychological Reactions in the Influence of Brand Experience on Brand Loyalty - Muhammad Rizki Zaldi; Agus David Ramdansyah; Yanto Azie Setya (P3M Trisakti School of Insurance (TSI), 2025)
This study investigates the mediating roles of brand trust and brand love in the relationship between brand experience and brand loyalty among Generation Y and Z users of the Tokopedia marketplace in Indonesia. Data were collected through an online questionnaire from 200 purposively selected respondents. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4 software. The findings reveal that brand experience does not have a direct effect on brand loyalty. However, brand experience has a significant positive effect on both brand trust and brand love. Brand trust significantly and positively influences both brand love and brand loyalty. Brand love also has a significant positive effect on brand loyalty. Furthermore, both brand trust and brand love serve as mediators in the relationship between brand experience and brand loyalty, both independently and simultaneously. These findings highlight key factors that can enhance brand loyalty to achieve competitive advantage and support the formulation of effective marketing strategies.